Attitudes Towards Death and Risk Behaviors in Students of a Public University in the State of Mexico - Moreno Jurado, Claudia Ivette (2019)
This study aimed at establishing the correlation between attitudes towards death and risk behaviors in psychology students of the State of Mexico. To this end, we used the PAM-R scale (1987) which evaluates attitudes towards death. According to Morales (2014), death is a natural process which every living being will have to experience and, therefore, just thinking about death may cause fear. We also used the YRBS questionnaire (2011) that evaluates risk behaviors. As stated by Le Breton (2012), the idea of death is present in risk behaviors, because individuals defy fear and convince themselves that they will always have an exit door, independently of the particular conditions they may deal with.